2014
DOI: 10.1108/ijchm-05-2013-0222
|View full text |Cite
|
Sign up to set email alerts
|

Do perceived CSR initiatives enhance customer preference and loyalty in casinos?

Abstract: Purpose – This study aims to investigate how perceptions associated with corporate social responsibility (CSR) initiatives influence customers’ preference and loyalty in a controversial consumer market. The mediating effect of brand preference between perceived CSR initiatives and customer loyalty is also examined. Design/methodology/approach – The methodology in the current study involves the use of questionnaire surveys delivered to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(36 citation statements)
references
References 81 publications
(110 reference statements)
3
31
2
Order By: Relevance
“…In this case, because of increasing awareness of environmental issues in the global hotel industry, consumers display strong purchase intention and positive behaviour towards organizations that adopt environmentally friendly practices (Kasim, 2004). Also, the significant positive link between customers' perception of the hotel stakeholder CSR and their positive eWOM confirms previous research that revealed how stakeholders' CSR activities affect customers' WOM (Liu et al, 2014b;Markovic et al, 2018). The explanation might be that customers, as hotel stakeholders, see CSR stakeholder activities relevant to themselves and therefore as more valuable (Liu et al, 2014b).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In this case, because of increasing awareness of environmental issues in the global hotel industry, consumers display strong purchase intention and positive behaviour towards organizations that adopt environmentally friendly practices (Kasim, 2004). Also, the significant positive link between customers' perception of the hotel stakeholder CSR and their positive eWOM confirms previous research that revealed how stakeholders' CSR activities affect customers' WOM (Liu et al, 2014b;Markovic et al, 2018). The explanation might be that customers, as hotel stakeholders, see CSR stakeholder activities relevant to themselves and therefore as more valuable (Liu et al, 2014b).…”
Section: Discussionsupporting
confidence: 78%
“…Regarding the link between stakeholders' CSR activites and customers' positive eWOM, Liu et al (2014b) found this to be more relevant, and therefore more valuable, to hoteliers. Vlachos et al (2009) similarly stated that CSR activities related to stakeholders could improve customer trust and reduce any scepticism about the organization, leading to stronger positive recommendations.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the context of shareholders, studies documented the CSR association with the corporate image (Ali, Danish, & Asrar‐ul‐Haq, 2020), reputation (Branco & Rodrigues, 2006; Javed, Rashid, Hussain, & Ali, 2020), and performance (Alafi & Hasoneh, 2012; Galbreath & Shum, 2012; Margolis, Elfenbein, & Walsh, 2009). From the customer perspective, studies examined the association between CSR and customer satisfaction (Lee & Heo, 2009; Saeidi, Sofian, Saeidi, Saeidi, & Saaeidi, 2015; Xie, Jia, Meng, & Li, 2017) and customer loyalty (Tingchi Liu, Anthony Wong, Rongwei, & Tseng, 2014). Past studies have also reported evidence about CSR and employee association through various behavior factors, that is, job satisfaction (Asrar‐ul‐Haq, Kuchinke, & Iqbal, 2017), organizational identification (Cheema, Afsar, & Javed, 2020), turnover intentions (Kim, Song, & Lee, 2016; Lin & Liu, 2017), and organizational commitment (Mory, Wirtz, & Göttel, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In literature, CSR is studied in varying industries, from various perspective, like environmental practices and green programs are major concern for hospitality industry as they directly influence corporate financial performance and value (Lee and Heo, 2009;Lee and Park, 2009). Further, in hotel industry, CSR is mostly studied for its consequences from customers' (Liu et al, 2014;Yueying, 2014;Lee et al, 2012), and/or firms' perspective Lee et al, 2013;Garay and Font, 2012; de Grosbois, 2012), but there is dearth of literature focusing on the employees' perspective (Fu et al, 2014;Lee et al, 2012).…”
mentioning
confidence: 99%